2011
DOI: 10.1016/j.ejso.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up reveals that ulceration and sentinel lymph node status are the strongest predictors for survival in patients with primary cutaneous melanoma

Abstract: , et al.. Long-term followup reveals that ulceration and sentinel lymph node status are the strongest predictors for survival in patients with primary cutaneous melanoma. EJSO -European Journal of Surgical Oncology, WB Saunders, 2011, 37 (8) This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
5
17
2
Order By: Relevance
“…Two large prospective studies, the Sunbelt Melanoma Trial [28] and the MSLT-1 [29•], have reported complications rates of 4.6 % and 10 %, respectively, in patients with SNB alone, as opposed to those undergoing completion LND (23.2 % and 37.2 %). Recent institutional series with long-term follow-up are consistent with earlier studies, showing complications rates of 6.9 % for SNB [16].…”
Section: Accurate Staging and Defining Prognosissupporting
confidence: 75%
See 1 more Smart Citation
“…Two large prospective studies, the Sunbelt Melanoma Trial [28] and the MSLT-1 [29•], have reported complications rates of 4.6 % and 10 %, respectively, in patients with SNB alone, as opposed to those undergoing completion LND (23.2 % and 37.2 %). Recent institutional series with long-term follow-up are consistent with earlier studies, showing complications rates of 6.9 % for SNB [16].…”
Section: Accurate Staging and Defining Prognosissupporting
confidence: 75%
“…A positive SNB has been consistently found to be one of the strongest prognostic factors in melanoma patients, followed by Breslow thickness, ulceration status [16,17] and, recently proposed, mitotic rate [18]. In Balch et al's [19•] recent study, nodal status as well as the extent of regional metastatic involvement [one positive sentinel node (N1a) compared to two or three sentinel nodes (N2a)] was shown to have significant prognostic value.…”
Section: Accurate Staging and Defining Prognosismentioning
confidence: 99%
“…Accordingly, the aim was to investigate whether the addition of TMR to the survival analysis caused any changes in the prognostic factors for survival established previously for this cohort. 6 As was the case for the association TMR and SLNB, increasing TMR was found to be a strong predictive factor for decreased survival univariately for all categorization methods and particularly for TMR method A. This finding could not be reproduced in a multivariate model for all TMR methods.…”
Section: Discussionmentioning
confidence: 69%
“…6 However, these analyses were conducted without taking the TMR into account. The current study aimed to investigate the predictive value of TMR and other current pathologic features of melanoma regarding sentinel lymph node status and melanoma survival.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] This discrepancy may be due to the difficulties associated with accurately identifying LVI with H&E staining alone, particularly in thick melanomas, where tumoral occlusion of vascular lumina can preclude LVI identification. Also, immunohistochemical staining is routinely used for SLN evaluation but not for LVI.…”
Section: Introductionmentioning
confidence: 99%